This is a difference of two squares.
Normal factorisation is (sum of roots)(difference of roots)
Or, if you prefer symbols:
a^2 - b^2 = (a+b)(a-b).
Here, b^8 = square of b^4
100 is square of 10
b^8 - 100 = (b^4 + 10)(b^4 - 10)
-----
the easy stuff ends here. If this is at the introduction level, then that is enough. If you are into higher level maths, then:
You could continue this, as long as you have "squares" and depending what you allow yourself to consider a "number"
b^4 - 10 = (b^2 + SQRT(10))(b^2 - SQRT(10))
b^2 - SQRT(10) = (b + root4(10))(b-root4(10))
where root4(10) means the 4th root of 10 (approximately 1.77828)
b^8 - 100 =
(b^4 + 10)(b^2 + SQRT(10))(b + root4(10))(b - root4(10))
-----
If you use complex numbers (where you are allowed to find square roots of negative numbers), you could continue with the other factor
b^4 + 10 = b^4 - (-10) = (b^2 + SQRT(-10))(b^2 - SQRT(-10))
(where the square root of -1 is normally indicated by the letter i ).
b^8 - 100 =
{b + [(i-1)*root4(5/2)]}*
{b + [(i-1)*root4(5/2)]}}*
{b+[(i+1)*root4(5/2)]}*
{b-[(i+1)*root4(5/2)]}*
{b + i*root4(10)}*{b - i*root4(10)}*
{b + root4(10)}*{b - root4(10)}
This would give you all eight complex roots of b^8-100, including the two that are real numbers.
2007-05-30 07:12:00
·
answer #1
·
answered by Raymond 7
·
1⤊
1⤋
Think of it as a difference of squares:
b^8 - 100
= (b^4)^2 - 10^2
= (b^4 + 10)(b^4 - 10)
In general, a difference of squares factors as follows:
a^2 - b^2 = (a + b)(a - b)
2007-05-30 07:09:25
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
This factors as the difference of squares.
(a² - b²) = (a + b)*(a - b) so
b^8 - 100 = (b^4 + 10)*(b^4 - 10) the 2'nd term can again be factored as
b^4 - 10 = (b² + √10)*(b² - √10) and, again, the 2'nd term can be further factored into
b² - √10 = (b + √√10)*(b - √√10) so the final factorization is
(b^4 + 10)*(b² + √10)*(b + √√10)*(b - √√10)
Doug
2007-05-30 07:12:44
·
answer #3
·
answered by doug_donaghue 7
·
0⤊
1⤋
This is typical of the method called difference of 2 squares
c² - d² = (c - d)(c + d)
so b^8 - 100 = (b^4 - 10)(b^4 + 10)
...................... = (b² - √10)(b² + √10)(b^4 + 10)
...................... = (b - 10^(1/4))(b + 10^(1/4)(b² + √10)(b^4 + 10)
2007-05-30 07:14:47
·
answer #4
·
answered by fred 5
·
0⤊
0⤋
First, multiply the -6 and you will do away with the parentheses -12b + -6 + 13b -7 = 0 Regroup and upload what you are able to (-12b + 13b) + (-6-7)=0 b-13=0 to do away with the 13 b-6+13=0+13 b=13
2016-10-30 05:38:11
·
answer #5
·
answered by ? 4
·
0⤊
0⤋
This is the difference of two squares.
b^8 - 100 = (b^4 - 10)(b^4 + 10)
If the power of b is even then you can always do this.
b^(2p) - r = (b^p + √r)(b^p - √r)
2007-05-30 07:10:58
·
answer #6
·
answered by peateargryfin 5
·
0⤊
1⤋
we use x^2-y^2=(x+y)(x-y)...........................(I)
b^8 - 100
=(b^4)^2-10^2
=(b^4+10)(b^4-10) [by (I)]
2007-05-30 07:17:31
·
answer #7
·
answered by chapani himanshu v 2
·
0⤊
1⤋